Assistance in the preparation of financial reports and asset inventory at BUMDes Wringinputih - Barkah Susanto; Eka Novia Susianti; Devi Hidayati; Suci Pangukir; Risa Yuliana Mahfiroh (Universitas Muhammadiyah Magelang, 2022)
During the Covid-19 pandemic, financial reports were prepared and asset data was collected in an effort to improve accountability and professionalism in the management of BUMDes. The Balkondes Guyub Rukun, Bojong Hamlet, Wringinputih Village, Borobudur District, Magelang Regency, was the venue of this program. A BUMDes manager and Balkondes Guyub Rukun employee, was the target of this program. Field surveys, problem identification, needs analysis, training, and mentorship are just a few of the activities that have been undertaken. It is envisaged that hosting activities and training in the preparation of financial reports and asset data collecting will provide insight and experience, as well as boost the efficacy of financial report preparation that is currently done manually. This program produces digital financial reports based on pivotable Excel spreadsheets and well-documented BUMdes asset inventory data.